Implementation of the Numbered Heads Together Learning Method in Improving Learning Outcomes of Islamic Religious Education or Character Education on the Material of Belief in the Messengers of Allah at SD Negeri 0719 Pir Sosa VI - Mustofa, Asyik; Priyatni, Ida; Azizah, Zahrotul; Nengsih, Wahyu; Wulandari, Nanda Ugig (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to determine the application of the Numbered Heads Together learning method in improving learning outcomes of Islamic Religious Education (PAI)/Characteristics on the material of believing in the Messengers of Allah in class IV of SD Negeri 0719 Pir Sosa VI Padang Lawas Regency. The method used in this study is an experimental method with an action class design. The subjects of the study were 25 class IV students. Data collection techniques were carried out through observation, learning outcome tests, and interviews. The results of the study showed that the application of the Numbered Heads Together method can increase students' active participation in learning and motivate students to be more enthusiastic in understanding the PAI/BP material about believing in the Messengers of Allah. In addition, the test results showed a significant increase in student learning outcomes after the application of this method. Therefore, it can be concluded that the use of the Numbered Heads Together method is effective in improving student learning outcomes on the material